The future of drug discovery : who decides which diseases to treat? - Bartfai, Tamas; Lees, Graham V. (London, UK : Academic Press, 2013)
'The Future of Drug Discovery: Who decides which diseases to treat? provides a timely and detailed look at the efforts of the pharmaceutical industry and how they relate, or should relate, to societal needs. The authors posit that as a result of increasing risk aversion and accelerated savings in research and development, the industry is not developing drugs for increasingly prevalent diseases, such as Alzheimer's disease, untreatable pain, antibiotics and more. This book carefully exposes the gap between the medicines and therapies we need and the current business path. By analyzing the situation and discussing prospects for the next decade, the The Future of Drug Discovery is a timely book for all those who care about the development needs for drugs for disease.' -- Publisher's website.
Why there will be new drugs despite the ongoing'crisis' of drug development in big pharma --The need for medicines grows -- Medicines are becoming better: some of the breakthrough medicines of the past decades -- Which diseases do we want to treat? -- Therapeutic Areas: strategically important diseases for the future -- Blockbuster proprietary drugs versus generic drugs -- Why is pharma a special industry? -- Diagnosing towards personalized medicine -- Personalized medicine -- How much can drugs cost? --Modeling Drug Discovery until 2025 -- Drug development models between 2010 & 2025.
Includes bibliographical references.
Keywords: Drug Discovery -- trends; Drug Industry -- economics; Drug development; Drugs -- Design